Evaluation of approximate methods to estimate maximum inelastic displacement demands. - Miranda, Eduardo (Earthquake engineering & structural dynamics.)
Six appropriate methods to estimate the maximum inelastic displacement demand of single degree of freedom systems are evaluated. In all methods, the maximum displacement demand of inelastic systems is estimated from the maximum displacement demand of linear elastic systems. Of the methods evaluated herein, four are based on equivalent linearization in which the maximum deformation is estimated as the maximum deformation of a linear elastic system with lower lateral stiffness and with higher damping coefficient than those of the inelastic system. In the other two methods the maximum inelastic displacement is estimated as a product of the maximum deformation of a linear elastic system with the same lateral stiffness and the same damping coefficient as those of the inelastic system for which the maximum displacement is being estimated, times a modifying factor. Elastoplastic and stiffness degrading models with periods between 0.05 and 3.0 s are considered when subjected to 264 ground motions recorded on firm sites in California. Mean ratios of approximate to exact maximum displacements corresponding to each method are computed as a function of the period of vibration and as a function of the displacement ductility ratio. Finally, comments on the advantages and disadvantages of each method when applied to practical situations are given.